2018
DOI: 10.1186/s13075-018-1624-x
|View full text |Cite
|
Sign up to set email alerts
|

Ten weeks of high-intensity interval walk training is associated with reduced disease activity and improved innate immune function in older adults with rheumatoid arthritis: a pilot study

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic inflammatory disease in which adults have significant joint issues leading to poor health. Poor health is compounded by many factors, including exercise avoidance and increased risk of opportunistic infection. Exercise training can improve the health of patients with RA and potentially improve immune function; however, information on the effects of high-intensity interval training (HIIT) in RA is limited. We sought to determine whether 10 weeks of a walking-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
148
5
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(171 citation statements)
references
References 69 publications
13
148
5
5
Order By: Relevance
“…But not only long term intervention has improvements also short term (12 weeks) studies showed total fat percentage reduction [65]. Nevertheless other short terms works (ten weeks) did not show reduction in total fat percentage with similar intensity and duration protocol [69] but in this study with older with rheumatoid arthritis.…”
Section: Discussioncontrasting
confidence: 47%
“…But not only long term intervention has improvements also short term (12 weeks) studies showed total fat percentage reduction [65]. Nevertheless other short terms works (ten weeks) did not show reduction in total fat percentage with similar intensity and duration protocol [69] but in this study with older with rheumatoid arthritis.…”
Section: Discussioncontrasting
confidence: 47%
“…Regarding body composition and anthropometric parameters, a study by Garcia Pinillos et al [15] found significant differences in body composition for older people ( − 2.15 % body mass, − 4.20 % fat mass, + 6.23 % muscle mass) after a 12-week low-volume HIIT-based concurrent training programme. However Ramirez et al [50], in a study with the same intensity of HIIT and the same duration of intervention did not find significant improvements in waist and hip circumference in adults with metabolic syndrome and Bartlett et al [5], in a recent study involving elderly people over 64 years, described no significant improvement in fat percentage after 10 weeks of HIIT intervention. On the other hand, very few studies have analyzed the effects of suspension training, especially in older adults, and thus a recent study performed on older women (aged 66.1 ± 4.7 years) showed that a 12-week suspension exercise training program led to significant decrease in percentage of fat mass, as well as in triceps, biceps and subscapular skinfolds [8].…”
Section: Discussionmentioning
confidence: 94%
“…These facts may be related to the short‐term exercise training adopted in our pilot analyze. In this way, 2 weeks of HIIT reduced TLR‐2 and TLR‐4 on monocyte cell surface and leukocyte chemokine receptors, while ten weeks of HIIT reduced the frequency of CD14 + CD16+ intermediate and CD14‐CD16 + monocytes . Thus, a more prolonged time of HIIT (>2 weeks) may be necessary to induce changes in CD4 + T cells activation markers and monocyte subsets.…”
Section: Discussionmentioning
confidence: 95%